The Contextualization of Catholic Theology in Vietnam: An Endeavor to Integrate Christian Faith within the Local Cultural and Religious Frameworks - Van Duong, Bien (Department of Comparative Study of Religions, 2025)
The article attempts to articulate the process of contextualization of Catholic theology in Vietnam from the early period to the end of the twentieth century. Through the efforts of both missionaries and Vietnamese theologians, contextual theology was established and attained certain results in the effort to integrate the Christian faith into the Vietnamese cultural and religious contexts. To make Catholicism harmonious with and integrate it into Vietnamese cultural and religious backgrounds, Vietnamese theologians even went further by endeavoring to build a contextual theology known as â€œViet-theologyâ€. In so doing, Catholic theologians contributed to effectively spreading their faith among Vietnamese people. Moreover, they help to build up religious tolerance in the context of multi-religious traditions like Vietnam.Â